KINERJA UMKM: KAJIAN SDM PADA FAKTOR PENDUKUNG DAN PENGHAMBAT SEBUAH SYSTEMATIC LITERATUR RIVIEW - Armi Dt.Mujua Batuah; Yulihardi Yulihardi; Jon Helmat Joni; Iim Fajriani; Zulpendi Zulpendi (Jurnal Ekonomi Bisnis Kompetif, 2026)
MSMEs are in important pillar of the national economy, yet many of their operators still struggle to face various challenges. This study aims to describe the supporting and inhibiting factors of MSMEs success through a Systemetic Literatur Review (SLR) of various national and international journals sourced from Gloogle Scholar and other journal portals. MSMEs rely on the application of digital technology, product innovation, human resources competence, as well as adequate access to capital. On the other hand, the progress of MSMEs is often hindered by low financial literacy, traditional management styles, and difficulties in penetrating wider markets. These finfings are expected to serve as practical guidance for MSMEs operators to improve, as well as a consideration for policymakers in designing more targeted support strategies